Neurostimulation Methods in the Treatment of Depression: A Comparison of rTMS, tDCS, and Venlafaxine Using a Pooled Analysis of Two Studies - Hejzlar M (Dove Medical Press, 2021)
Martin Hejzlar,1,2 Tomas Novak,1,2 Martin Bares1,2 1NIMH Clinical Center, National Institute of Mental Health Czech Republic, Klecany, Czech Republic; 2Department of Psychiatry and Medical Psychology, Third Medical Faculty, Charles University, Prague, Czech RepublicCorrespondence: Martin HejzlarNational Institute of Mental Health Czech Republic, Topolova 748, Klecany, 250 67, Czech RepublicTel +420 283 088 314Email Martin.Hejzlar@nudz.czBackground: There are no head-to-head studies comparing the antidepressant effect of transcranial direct current stimulation (tDCS) with repetitive transcranial magnetic stimulation (rTMS). This pooled analysis compared indirectly the antidepressant efficacy and acceptability of rTMS, tDCS, and the antidepressant venlafaxine (VNF) extended-release.Methods: The analysis (n=117, both patients with treatment-resistant depression (TRD) and non-TRD were included) examined pooled data from two 4-week, single-centered, two-armed, double-blind, randomized studies (EUDRACT n. 2005-000826-22 and EUDRACT n. 2015-001639-19). The antidepressant efficacy of right-sided low-frequency rTMS (n=29) vs VNF (n=31) and left-sided anodal tDCS (n=29) vs VNF (n=28) was evaluated. The primary outcome was a change in the Montgomery–Åsberg Depression Rating Scale (MADRS) score from baseline to the treatment endpoint at week 4. The response was defined as a ≥ 50% reduction in the MADRS score and remission as the MADRS score ≤ 10 points, both were calculated for the primary treatment endpoint at week 4.Results: Mean change in total MADRS scores from baseline to week 4 was 7.0 (95% CI, 4.8– 9.1) points in the rTMS group, 7.6 (95% CI, 5.5– 9.8) in the tDCS group, and 8.9 (95% CI, 7.4– 10.4) among patients in the VNF group, a non-significant difference (F(2111)=0.62, p=0.54). Similarly, neither the response rates nor remission rates for rTMS (response 31%; remission 17%), tDCS (24%, 17%), or VNF (41%; 27%) significantly differed among treatment groups (χ2=2.59, p=0.28; χ2=1.66, p=0.44). Twenty patients (17%) dropped out of the studies in a similar proportion across groups (rTMS 3/29, tDCS 6/29, VNF 11/59, χ2=1.41, p=0.52).Conclusion: Our current analysis found a comparable efficacy and acceptability in all three treatment modalities (rTMS, tDCS, and VNF) and clinical relevance for the acute treatment of major depressive disorder.Keywords: repetitive transcranial magnetic stimulation, rTMS, transcranial direct-current stimulation, tDCS, venlafaxine, major depressive disorder, MDD, treatment, efficacy